2003
DOI: 10.1002/ajh.10339
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MTHFR, GSTM1, GSTT1, GSTP1, and CYP1A1 genotypes in childhood acute leukemia

Abstract: The role of methylenetetrahydrofolate reductase (MTHFR C677T), glutathione Stransferases (GSTM1 and GSTT1 null, GSTP1 Ile105Val), and cytochromes p450 (CYP1A1*2A) genotypes in the etiology of childhood leukemia was simultaneously investigated. 144 Turkish children with acute lymphoblastic leukemia (ALL) and 33 with acute nonlymphoblastic leukemia (ANLL) were studied and compared with 185 healthy pediatric controls. The frequency of MTHFR genotype was insignificantly higher in ALL (7.7%) and ANLL (6.3%) than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 20 publications
2
78
3
Order By: Relevance
“…CYP 1A1*2A allele frequency has been found to be significantly increased in children with ALL as compared to normal controls in a French-Canadian population (OR ¼ 1.8; 95% CI, 1.1, 3.1) [16]. However, there is no difference in this allele frequency between Turkish children with ALL and healthy volunteers [17]. Our Thai population has a high prevalence of CYP 1A1*2A and *2B variants when compared to Caucasians or African Americans [18].…”
Section: Discussionmentioning
confidence: 91%
“…CYP 1A1*2A allele frequency has been found to be significantly increased in children with ALL as compared to normal controls in a French-Canadian population (OR ¼ 1.8; 95% CI, 1.1, 3.1) [16]. However, there is no difference in this allele frequency between Turkish children with ALL and healthy volunteers [17]. Our Thai population has a high prevalence of CYP 1A1*2A and *2B variants when compared to Caucasians or African Americans [18].…”
Section: Discussionmentioning
confidence: 91%
“…CYP1 family enzyme expressions are increased in myeloblastic and lymphoid cell lines, and CYP1 enzymes may contribute to the carcinogenesis of hematopoietic cells [5]. Several groups found that CYP1A1*2 variant allele was not related with childhood acute leukemias [36,52], whereas Sinnett et al showed CYP1A1*2A is one of the significant risk determinants of ALL [31]. Another study from Turkey found homozygous CYP1A1*2A genotype to be under-represented in ALL patients as compared to controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…Published data indicate that xenobiotic-metabolizing polymorphic alleles in some populations correlate with increased risk of different lymphoproliferative diseases [18][19][20][21][22]. The majority of articles were devoted to the analysis of acute leukemia and, particularly, childhood leukemia [21,[23][24][25]. Thus, it would be interesting to investigate associations between polymorphous variants of xenobiotic-metabolizing genes and risk of development of other lymphoproliferative diseases.…”
Section: Introductionmentioning
confidence: 99%